Chemical characteristics of the ripe guava fruit (Psidium guajaba L.) silage for their use in pigs under the Ecuadorian Amazon conditions - Caicedo, W.; Valle, S.; Caicedo, L.; Caicedo, María (Cuban Journal of Agricultural Science, 2023)
At present, the conventional raw matters for the elaboration of balanced (concentration) pig diets have been notably increase, so it is necessary to use resources of alternative feeding to achieve sustainable productions. Considering the reality, the chemical characteristics of the ripe guava fruit silage as alternative food for pigs are evaluated in this study. In eight days silage samples was determined the dry matter, crude protein, crude fiber, ether extract, ashes, nitrogen free extracts and gross energy. In the days 0, 1, 4, 8, 15 and 30 the pH was determined. In the nutritional composition (dry matter, crude protein, crude fiber, ether extract, ashes, nitrogen free extracts and gross energy) the average value, standard deviation and variation coefficient was checked. The pH data were processed through a completely random design, where the treatments were the fermentation days (0, 1, 4, 8, 15 and 30 d).At day eight of evaluation; the silage has considerable contents of dry matter (22.61 %), crude protein (13.51 %), crude fiber (9.90 %), ether extract (6.08 %), ash (10.24 %), nitrogen free extract (72.49 %) and gross energy (18.54 kJ g DM-1). With respect to the pH, the highest values (p < 0.05) were showed in the day 0 (4.75) and one (4.01), and between the days 4 and 30 was stabilized (3.74-3.76). The ripe guava fruit silage showed good nutritional composition and constitutes an alternative food with favorable nutritive characteristics for their use in pig diets under the Ecuadorian Amazonia conditions. Key words: alternative food, pigs, fermentation, tropical fruit.